Assessment and management of health status in full life cycle of echelon utilization for retired power lithium batteries. (15th December 2022) - Chen, Haopeng; Zhang, Tianshi; Gao, Qing; Han, Zhiwu; Jin, Yingai; Li, Liang; Yang, Kaiqiao; Xu, Yihuai; Liu, Xiaoyan; Xu, Xiaoyu; Wang, Shengshi
Abstract: In recent years, a significant increase in market share has occurred in the global electric vehicle industry. These advancements will eventually lead to a large-scale decommissioning of power batteries. Global governments are actively promoting echelon utilization of retired power lithium batteries, enacting a series of policies and incentives, and the industry has also constructed large-scale projects in line with national strategies to extend the life cycle of retired power batteries. While echelon utilization for retired power lithium batteries is complex, it involves scientific assessment and management of battery health in the full life cycle. This paper summarizes relevant studies and technical progress and reconstructs a health assessment system for the full life cycle of echelon utilization for retired power lithium batteries. By extending the definition of battery health status and improving the assessment index of battery health status, the paper proposes an analysis method of health status in multi-scale, multi-dimensional, and multi-physical fields. We also analyze safety accident reports of energy storage plants, summarize the main factors that affect battery health, and propose a solution for integrated multi-stage and multi-level battery health management throughout the life cycle. Electricity and thermal management are core foundations and humidity, dust, and salt spray management for various geographical and climatic conditions. These technologies can be fully integrated with bionic principles in future studies. With the support of global governments, gradual implementation of supporting policies, and continuous advances in management and core technologies of battery health in the full life cycle of echelon utilization for retired lithium batteries, related industries will develop rapidly in the next five to ten years. Highlights: Reconstructing an assessment system for the full life cycle of echelon utilization. Extending the definition of battery health status. Improving the assessment index of battery health status. Proposing a method in multi-scale, multi-dimensional, and multi-physical fields. Proposing a solution for integrated multi-stage and multi-level health management.